Uncle Rico's encore mostly true stories of Filipino Seattle - Bacho, Peter (Seattle University of Washington Press, 2022)
"From the 1950s through the 1970s, blue-collar Filipino Americans, or Pinoys, lived a hardscrabble existence. Immigrant parents endured blatant racism, sporadic violence, and poverty while their US-born children faced more subtle forms of racism, such as the low expectations of teachers and counselors in the public school system. In this collection of autobiographical essays, acclaimed novelist and short-story writer Peter Bacho centers the experiences of the Pinoy generation that grew up in Seattle's multiethnic neighborhoods, from the Central Area to Beacon Hill to Rainier Valley. He recounts intimate moments of everyday life: fishing with marshmallows at Madison Beach, playing bruising games of basketball at Madrona Park, and celebrating with his uncles in Chinatown as hundreds of workers returned from Alaska canneries in the fall. He also relates vivid stories of defiance and activism, including resistance to the union-busting efforts of the federal government in the 1950s and organizing for decent housing and services for elders in the 1970s. Sharing a life inextricably connected to his community and the generation that came before him, this memoir is a tribute to Filipino Seattle"--
Keywords: Bacho, Peter; Filipino Americans -- Biography; Filipino American authors -- 20th century -- Biography